Customer Perceptions of Innovativeness: An Accelerator for Value Co-Creation. (August 2019) - Kim, Eojina; Tang, Liang (Rebecca); Bosselman, Robert
Hospitality and tourism businesses engage customers as collaborators in creating value through the satisfactory delivery of products and services. The purpose of this study is to examine the effect of customers' perception of innovativeness on their value co-creation behavior. Specifically, with the theoretical support of Service-Dominant logic, the present study investigates customer value co-creation behavior, its antecedents (i.e., customer's perceived innovativeness) and consequences (i.e., customer satisfaction and loyalty) at restaurants. This study confirms a holistic concept of perceived innovativeness as the key predictor of customers' behavior for value co-creation, which in turn leads to their satisfaction and loyalty. This study contributes to the evolving knowledge of innovativeness and value co-creation and offers practitioners effective strategies to improve customer value co-creation behavior through their perceptions of restaurants' innovativeness and thereby maximizing their satisfaction and loyalty.